Unveiling alliinase gene candidates in shallots using resistance gene motif-based degenerate primers - Herlina, Lina; Istiaji, Bonjok (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Shallots are integral to Indonesian daily life, with annual production reaching two million tons. However, the superior varieties are often susceptible to disease, highlighting the need for new resistant varieties. Understanding the genetic basis of disease resistance is crucial for breeding efforts aimed at developing new varieties. Alliinase, an enzyme crucial for garlic defense, is a potential candidate for enhancing shallot resistance. This study aims to identify alliinase gene candidates in shallots using degenerate primers. Genomic DNA from the Bima Brebes genotype was isolated, and degenerate primers successfully amplified 600–800 bp fragments. Three sequences were selected for further analysis, with one sequence showing high similarity to known resistance genes. Multiple sequence alignment revealed characteristic resistance gene motifs, supporting their candidacy as resistance genes. Phylogenetic analysis grouped these sequences with known resistance genes, further supporting their potential. These findings provide valuable insights for breeding programs aiming to enhance resistance in shallots through a molecular breeding approach. The identified alliinase gene candidates can be used to develop disease-resistant shallot varieties. Incorporating these genes into breeding programs can enhance resistance, improving yield and stability in shallot production.